Pengaruh media pendingin terhadap kekerasan dan ketangguhan hasil pengelasan material AISI 1050 pada proses las MAG - Azwinur Azwinur; Muhammad Yudi; Zulkifli Zulkifli (Jurnal POLIMESIN, 2020)
The temperature of the cooling medium is a substance that serves to determine the speed of the cooling process of the material that has been given heat treatment from the welding results. Cooling is an alternative to improve and improve the mechanical properties of post-welding materials. The selection of the temperature of the cooling medium is very important to get a good connection strength. The purpose of this study was to determine the effect of the cooling media on the hardness and toughness of AISI 1050 material using the MAG welding process. The cooling media which are varied are water, sea water, and air. The welding process used is the welding process MAG (Metal active gas) with CO2 protective gas, the material used type AISI 1050 with mechanical testing hardness and impact test. The results showed that the use of the type of cooling media affects the strength of the welding joint in terms of the value of the hardness and toughness of the material receiving the load. The highest hardness value in the HAZ 1, HAZ 2 and weld metal areas occurs in the use of sea water cooling media where in HAZ 1 is 71, 63, HAZ 2 is 73.5 and weld metal is 70, while the lowest value in the use of air conditioning media where on HAZ 1 of 65.63, HAZ 2 of 63.75 and weld metal of 58.83. The impact toughness test results found that the use of seawater cooling media has the highest toughness value of 1.83 joules / mm², then followed by air media of 1.75 joules / mm², and the lowest is the water use of 1.50 joules / mm² .